ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Dwi Indah Wulandari, 15.05.52.0246; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze the effect of Profitability, Capital structure, Company Growth, and Company size on Company Value. The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2015-2017 Period. The sample selection uses the purpose sampling method so that the sample is 198 data. The analytical tool used in this study is descriptive analysis and multiple regression analysis. The test results show that the variable profitability and size of the company have a positive effect on compony value. While the capital structure variable has a negative effect on compony value, then the growth of the company does not affect the value of the company.